Characterizing heterogeneous intragranular deformations in polycrystalline solids using diffraction-based and mechanics-based metrics. (17th May 2017) - Carson, Robert; Obstalecki, Mark; Miller, Matthew; Dawson, Paul
Abstract: Deformations within and among crystals have been observed to be heterogeneous for most structural alloys whether the alloys are subjected to monotonic or cyclic loading. Over a material's loading history, these intragrain deformations influence how failure mechanisms activate. A series of finite element simulations were conducted for a completely reversed loading cycle applied to a precipitation hardened copper alloy. The simulations were conducted using different hardening assumptions within a single crystal, elasto-viscoplastic constitutive model. The results were used to develop several intragrain heterogeneity metrics applicable to both measured and computed data. The computed metrics are shown to correlate strongly with the corresponding values derived from x-ray diffraction experiments. The intragrain heterogeneity metrics provide an effective tool to quantitatively measure and compare the influence of different constitutive models under the same loading conditions. This is demonstrated for the differences in deformation heterogeneity between isotropic and anisotropic hardening assumptions under cyclic loading.